Antibiotic use during pregnancy alters the commensal vaginal microbiota. (18th November 2013) - Stokholm, J.; Schjørring, S.; Eskildsen, C. E.; Pedersen, L.; Bischoff, A. L.; Følsgaard, N.; Carson, C. G.; Chawes, B. L. K.; Bønnelykke, K.; Mølgaard, A.; Jacobsson, B.; Krogfelt, K. A.; et al.
Abstract Antibiotics may induce alterations in the commensal microbiota of the birth canal in pregnant women. Therefore, we studied the effect of antibiotic administration during pregnancy on commensal vaginal bacterial colonization at gestational week 36. Six hundred and sixty‐eight pregnant women from the novel unselected Copenhagen Prospective Studies on Asthma in Childhood (COPSAC2010) pregnancy cohort participated in this analysis. Detailed information on oral antibiotic prescriptions during pregnancy filled at the pharmacy was obtained and verified prospectively. Vaginal samples were obtained at pregnancy week 36 and cultured for bacteria. Women who received oral antibiotics during any pregnancy trimester had an increased rate of colonization by Staphylococcus species in the vaginal samples as compared with samples obtained from women without any antibiotic treatment during pregnancy (adjusted OR 1.63, 95% CI 1.06–2.52, p 0.028). Oral antibiotic administration in the third trimester were also associated with increased colonization by Staphylococcus species (adjusted OR 1.98, 95% CI 1.04–3.76, p 0.037). These bacteriological changes were associated with urinary tract infection antibiotics. Women treated in the third trimester of pregnancy were more often colonized by Escherichia coli than women without antibiotic treatment in the third trimester (adjusted OR 1.91, 95% CI 1.04–3.52, p 0.038). This change was associated with respiratory tract infection (RTI) antibiotics. We did not observe any significant changes in vaginal Streptococcus agalactiae (group B streptoccocus) or Staphylococcus aureus colonization following antibiotic treatment in pregnancy. Antibiotic administration during pregnancy leads to alterations in the vaginal microbiological ecology prior to birth, with potential morbidity, and long‐term effects on the early microbial colonization of the neonate.